لجان المراجعة كاقتراح للتضييق من فجوة التوقعات في مهنة المراجعة بالجزائر – دراسة ميدانية - - خالدي, رشيدة (جامعة الوادي - University of Eloued, 2015)
إن مشكلة فجوة التوقعات من المشاكل الحديثة التي أثارت اهتمام العديد من المهنيين والباحثين في مجال المحاسبة والمراجعة، خاصة بعد فشل كبرى الشركات العالمية مثل: شركة أنرون وشركة ورلد كوم، هذه الفجوة لا يمكن تجاهلها أو الإدعاء أن توقعات مستخدمي القوائم المالية غير واقعية، ولهذا يجب أن توجه الجهود لدراسة العوامل التي أدت إلى وجود تلك الفجوة وعمل اقتراحات وتوصيات بناءة من شأنها التضييق أقصى حد ممكن من هذه الفجوة، حيث يعتبر وجود لجان المراجعة في المؤسسة من بين الوسائل التي تساعد على التضييق من فجوة التوقعات من خلال تفعيل آلياتها، خاصة من خلال الدور الذي تلعبه هذه اللجان في دعم استقلال مراجع الحسابات. The problem of the expectations is of among modern problems that aroused the interest of many professionals and researchers in the field of accounting and auditing, especially after the major international companies fail, such as Enron Corp. and WorldCom, this gap cannot be ignored or claim that users of financial statements unrealistic expectations gap, so, must be directed efforts to study the factors that led to the existence of the gap and work proposals and recommendations constructive that will restrict the maximum extent possible from this gap, it is the presence of audit committees in the organization of the means that help narrowing of the expectations gap by activating its mechanisms, particularly through the role played by these committees in support of the independence of the auditor.
مقال
Keywords: فجوة التوقعات، مهنة المراجعة في الجزائر; The expectations gap, the audit profession in Algeria